Novel space alters theta and gamma synchrony across the longitudinal axis of the hippocampus - penley, stephanie c.; hinman, james r.; long, lauren l.; markus, etan j.; escabi, monty a.; chrobak, james j. (Frontiers in Systems Neuroscience, 2013)
Hippocampal theta (6-10 Hz) and gamma (25-50 Hz and 65-100 Hz) local field potentials reflect the dynamic synchronization of inputs impinging upon hippocampal neurons. Novel experience is known to engage hippocampal physiology and promote successful encoding. Does novelty synchronize or desynchronize theta and/or gamma frequency inputs across the septotemporal (long) axis of the hippocampus? The present study tested the hypothesis that a novel spatial environment would alter theta power and coherence across the long axis. We compared theta and gamma local field potential signals at individual (power) and millimeter distant electrode pairs (coherence) within the dentate gyrus (DG) and CA1 region while rats navigated a runway 1) in a familiar environment, 2) with a modified path in the same environment and 3) in a novel space. Locomotion in novel space was related to increases in theta and gamma power at most CA1 and DG sites. The increase in theta and gamma power was concurrent with an increase in theta and gamma coherence across the long axis of CA1; however, there was a significant decrease in theta coherence across the long axis of the DG. These findings illustrate significant shifts in the synchrony of entorhinal, CA3 and/or neuromodulatory afferents conveying novel spatial information to the dendritic fields of CA1 and DG targets across the long axis of the hippocampus. This shift suggests that the entire theta/gamma-related input to the CA1 network, and likely output, receives and conveys a more coherent message in response to novel sensory experience. Such may contribute to the successful encoding of novel sensory experience.